Initial Observations by the GOLD Mission. Issue 7 (26th June 2020) - Eastes, R. W.; McClintock, W. E.; Burns, A. G.; Anderson, D. N.; Andersson, L.; Aryal, S.; Budzien, S. A.; Cai, X.; Codrescu, M. V.; Correira, J. T.; Daniell, R. E.; Dymond, K. F.; et al.
Abstract: The NASA Global‐scale Observations of the Limb and Disk (GOLD) mission has flown an ultraviolet‐imaging spectrograph on SES‐14, a communications satellite in geostationary orbit at 47.5°W longitude. That instrument observes the Earth's far ultraviolet (FUV) airglow at 134–162 nm using two identical channels. The observations performed include limb scans, stellar occultations, and images of the sunlit and nightside disk from 6:10 to 00:40 universal time each day. Initial analyses reveal interesting and unexpected results as well as the potential for further studies of the Earth's thermosphere‐ionosphere system and its responses to solar‐geomagnetic forcing and atmospheric dynamics. Thermospheric composition ratios for major constituents, O and N2, temperatures near 160 km, and exospheric temperatures are retrieved from the daytime observations. Molecular oxygen (O2 ) densities are measured using stellar occultations. At night, emission from radiative recombination in the ionospheric F region is used to quantify ionospheric density variations in the equatorial ionization anomaly (EIA). Regions of depleted F region electron density are frequently evident, even during the current solar minimum. These depletions are caused by the "plasma fountain effect" and are associated with the instabilities, scintillations, or "spread F " seen in other types of observations, and GOLD makes unique observations for their study. Plain Language Summary: The NASA Global‐scale Observations of the Limb and Disk (GOLD) mission has flown a dual‐channel, ultraviolet‐imaging spectrograph on SES‐14, a communications satellite in geostationary orbit at 47.5°W longitude. That instrument observes the Earth's far ultraviolet (FUV) airglow at 134–162 nm. The observations performed include images of the Earth's sunlit and nightside disk, limb scans, and stellar occultations, from 6:10 to 00:40 universal time each day. Initial analyses reveal interesting and unexpected results as well as the potential for further studies of the Earth's thermosphere‐ionosphere system and its responses to solar‐geomagnetic forcing and atmospheric dynamics. Thermospheric temperatures and composition ratios for major constituents, O and N2, near 160‐km altitude and exospheric temperatures are retrieved from the daytime observations. Molecular oxygen (O2 ) densities are measured using stellar occultations. At night, emission from radiative recombination in the ionospheric F region is used to quantify ionospheric density variations in the equatorial ionization anomaly (EIA). Regions of depleted F region electron density are frequently evident in the EIA, even during the current solar minimum. Key Points: GOLD makes global‐scale, synoptic measurements of the temperature, composition, and densities in the thermosphere‐ionosphere system Most measurements by the GOLD instrument are made in one of four modes The observations are providing new and surprising insights into the characteristics and behavior of the thermosphere and ionosphere